PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Abelia Maulani; Lita Permata Sari; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to analyze the effect of capital structure, liquidity, and firm size on firm value, with profitability as an intervening variable. The object of this study is manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The sampling technique used is purposive sampling, with a total sample of 13 companies. The data analysis method is carried out using Smar:PLS 3.0. The analysis procedures include classical assumption tests (normality test and multicollinearity test), coefficient of determination (R²) test, structural model analysis (inner model), and hypothesis testing. The results of the direct hypothesis testing show that capital structure has a significant negative effect on profitability, liquidity has a negative but not significant effect on profitability, and firm size has a significant negative effect on profitability. Furthermore, capital structure has a significant positive effect on firm value, while liquidity and firm size have positive but not significant effects on firm value. Profitability is proven to have a significant positive effect on firm value. Meanwhile, the results of the indirect hypothesis testing indicate that capital structure and firm size have a significant negative effect on firm value through profitability. On the other hand, liquidity has a negative but not significant effect on firm value through profitability